Becoming Cajun, Becoming American : The Acadian in American Literature from Longfellow to James Lee Burke - Hebert-Leiter, Maria (Book collections on Project MUSE., 2009)
From antebellum times, Louisiana's unique multipartite society included a legal and social space for intermediary racial groups such as Acadians, Creoles, and Creoles of Color. In Becoming Cajun, Becoming American, Maria Hebert-Leiter explores how American writers have portrayed Acadian culture over the past 150 years. Combining a study of Acadian literary history with an examination of Acadian ethnic history in light of recent social theories, she offers insight into the Americanization process experienced by Acadians-who over time came to be known as Cajuns-during the nineteenth and twentiet.